(3JeKGd GdCeKGds - (3GdTjHj , eMeO Hf Ydj Hf eMeO Hf CHj HcQ GdbQTj Gdecj GdTGaYj GdYHOQj, LeGd GdOjf CHh GdeMGSf,J (B837 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefRg Yf GdeKd hdg GdeKd , GdCYdi GdYdi GdPi eG TGA UfY heG GQGO aYd hHYO agPg CeKGd djS dgG eKd , hahGFO cGdLhGgQ haQGFO cGddBdi s
(3BNQgG (B:s
(3BNQg ai TQM GdeKd (B" (3jhe Hjhe GdMaUd GdeLhQ (B" (3ahKHhG Ydi Yege aTcG Pdc Edi CNjg heKdg VQH jVQH Je cJGH JeKGd GdCeKGd s
(3HgG fXGe GdJYbjHIs
(3QJHg eUfag Ydi MQha GdeYLes
(3hTQM cd eKds
(3hGSJbUi eG bGdg GdSGHbhf Ydjg ajg s
(3cJHJ GdCeKGd hGdCHhGH HGdMeQI s
(3hYdi GdfSNI JedcGJ HYVgG ZjQ eDQN hHYVgG eMOK s
Keywords: (3GdCOHs